ANALYSIS OF SOME OF THE ISSUES OF EXPANDING THE SUBJECT OF A LOAN AGREEMENT - Sohibjon Gaibullayev (Scholar Express Journals, 2024)
The article analyzes the concept, value of the loan agreement and issues related to its application. The article also considers the expansion of the scope of the subject of the loan agreement and develops proposals to improve the legislation on debt.
Keywords: Debt; contract; goods; money